TEACHING AND LEARNING WITH “EVERYTHING THAT WE CAN POSSIBLY SEE” IN THE LANDSCAPES OF THE CITY. - Basílio, Edvar Ferreira; Castro, Edna Ribeiro de; Feitosa, Adriana Madja dos Santos; Ribeiro, Luis Távora Furtado (Geosaberes; Vol 14 (2023)DO - 10.26895/geosaberes.v14i0.1208, 2023)
The objective of this study is to provide a (re) construction of the teaching practices and knowledge in Geography in Elementary School - Early Years, through the teaching and learning methodology of reading and interpreting landscapes in urban spaces. This qualitative research has as main bibliographic and documentary sources the studies of Santos (1997, 2012), Callai (2018), Cavalcanti (2019), Straforini (2021), Claudino (2023) and the BNCC (2018), taking the city of Fortaleza-CE as a socio-spatial parameter. The promotion of educational processes based on the everyday reality of the student is a useful methodological alternative for the development of interdisciplinary knowledge guided to the formation of active citizenships.